Balance de la vanguardia literaria en Trilce - Tello C., Olga Judith (2019)
Analyzes Trilce (1922), the second book of poems by César Vallejo that revolutionized the spaces of Peruvian and Latin American literary criticism and generated confusion over the radical transformation of poetic language. Representative of the break with traditional aesthetics, with the insufficiency of established poetic discourse. The research suggests that it is a particular creation, however, it contains elements that coincide with the literary avant-garde of the time and poetic writing transcends and creates new art.